2008
DOI: 10.1016/j.amjmed.2008.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Overweight, Obesity, and Elevated Serum Cystatin C Levels in Adults in the United States

Abstract: Background-Although high body mass index (BMI) is a risk factor for hypertension, diabetes, and cardiovascular disease, limited data exist on the association of overweight and obesity with early stages of kidney disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
83
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(101 citation statements)
references
References 23 publications
14
83
1
3
Order By: Relevance
“…Several studies indicate that increased body weight and obesity are associated with elevated serum cystatin C concentrations (13,14,15,17). The results presented here ( fig.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Several studies indicate that increased body weight and obesity are associated with elevated serum cystatin C concentrations (13,14,15,17). The results presented here ( fig.…”
Section: Discussionsupporting
confidence: 71%
“…Several recently reported studies indicate that increased body weight and obesity are associated with elevated serum cystatin C concentrations (13)(14)(15)(16)(17). For instance, a positive correlation betwen serum cystatin C concentrations and BMI has been reported (13,14,15).…”
mentioning
confidence: 93%
“…Reference values for cystatin-C have shown to be between 0.52 and 0.98 mg/L with a standard deviation of 0.19 mg/L. 20 Elevated serum cystatin-C was defined as !1.09 mg/L at the study of Muntner et al 21 At least one SD elevation was assumed to be different among groups with regard to that paper. 21 Post-hoc power analysis revealed that this study has a power of 84% with these values.…”
Section: Discussionmentioning
confidence: 99%
“…20 Elevated serum cystatin-C was defined as !1.09 mg/L at the study of Muntner et al 21 At least one SD elevation was assumed to be different among groups with regard to that paper. 21 Post-hoc power analysis revealed that this study has a power of 84% with these values. Power analysis was performed using the G*Power software (G*Power Version 3.1.5, Kiel, Germany).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that BMI is related to the serum levels of cystatin C (17)(18)(19). The mechanism of this association is unclear, but experimental evidence suggests that adipocyte tissues secrete large amounts of cystatin C, which can lead to the increased levels of serum cystatin C in obese individuals with high BMI (20).…”
Section: Introductionmentioning
confidence: 99%